Portrait of Education Aspects in Indonesia During the Japanese Occupation (1942-1945) - Dadan Adi Kurniawan; Syaffrina Fadhilatul Nikmah; Nasta Ayundra Oktavian Mahardi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This article discusses a portrait of the development of educational institutions during the Japanese occupation in Indonesia in 1942-1945. The aspects of education include the level of education, the language of education, access to education, the cover and contents of textbooks, types of subjects, infrastructure, students and teachers, the heritage of semi-militaristic education, and the general goals of Japanese education in Indonesia. This research is important to find out the continuity regarding the heritage of Japanese education that still alive today. This research uses a historical method that includes four main stages, which are heuristics, criticism, interpretation, and historiography. Data collection techniques use literature studies (library studies) in the form of books, theses, journals, and articles. The research results show that educational principles during the Japanese occupation tended to be contradictory compared to education in the Dutch colonial era. Education in Indonesia during the Japanese occupation was no longer discriminatory but inclusive (open to all people). The education of the Japanese occupation was not intellectualistic but rather semi-militaristic which prioritized physical fitness and agility. Education became a means of mobilization and a means of indoctrination in makes people who were ready to support the victory of Japan's war against the Allies in the Pacific and make Japan the leader of Greater East Asia.